2010
DOI: 10.1259/bjr/35714052
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of colonic volvulus: findings on multidetector CT with three-dimensional reconstructions

Abstract: ABSTRACT. Large bowel volvulus is a rare condition that can occur in patients who present with acute abdominal pain. Radiologists should be able to recognise its appearance on multidetector CT (MDCT) images so that the correct diagnosis can be made and catastrophic consequences can be avoided. In this article, we discuss and illustrate the MDCT and three-dimensional appearance of the various forms of large bowel volvulus. As MDCT allows the precise diagnosis of topography, mechanism and severity, this techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 12 publications
0
22
0
5
Order By: Relevance
“…However, colonic wall necrosis was reported in another dog at surgery where colonic wall enhancement was considered normal on CT. In human patients, precontrast hyperattenuation of the colonic wall secondary to transmural hemorrhagic necrosis, colonic wall thickening, poor enhancement of the colonic wall, and pneumatosis coli are all findings that may be used to predict colonic wall viability . Further investigations are required in order to investigate whether CT findings may help predict the degree of torsion and colonic wall viability in dogs with colonic torsion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, colonic wall necrosis was reported in another dog at surgery where colonic wall enhancement was considered normal on CT. In human patients, precontrast hyperattenuation of the colonic wall secondary to transmural hemorrhagic necrosis, colonic wall thickening, poor enhancement of the colonic wall, and pneumatosis coli are all findings that may be used to predict colonic wall viability . Further investigations are required in order to investigate whether CT findings may help predict the degree of torsion and colonic wall viability in dogs with colonic torsion.…”
Section: Discussionmentioning
confidence: 99%
“…Only and pneumatosis coli are all findings that may be used to predict colonic wall viability. 29 Further investigations are required in order to investigate whether CT findings may help predict the degree of torsion and colonic wall viability in dogs with colonic torsion.…”
Section: Only Two Dogs Demonstrated Small Intestinal Distension Whereasmentioning
confidence: 99%
“…31,32 A study among Nigerian children reported the anatomical site incidence of IV as 82% for jejunoileal volvulus, 14% for sigmoid volvulus and 4% for caecal volvulus. In adults, volvulus of the sigmoid colon accounts for the majority of cases (60%).…”
Section: Discussionmentioning
confidence: 99%
“…abdomen pueden sugerir el diagnóstico, pero su presentación es inconstante (5,11,12). En cuanto a la tomografía, una revisión realizada por Vandendries y colaboradores no reportó características radiológicas propias para el vólvulo del colon transverso (9).…”
Section: Discussionunclassified